Beyond the Name: Analysis of Cohesion Factor in Name Congruence and Socioemotional Wealth Relation of Family Business - Day, Steven W.; Aiyede, John (Journal of Applied Business and Economics, 2023)
In the forthcoming study, our overarching objective is to embark on a comprehensive exploration of the intricate linkages between the family name and the socioemotional wealth intrinsic to family businesses. This investigation places a specific emphasis on unraveling the mediating role played by family cohesion in shaping these complex dynamics. Our theoretical endeavor seeks to make a distinctive contribution to the scholarly landscape by providing nuanced insights into the multifaceted relationships within family businesses. By anchoring our study in the foundation of established literature, our aim extends beyond expanding empirical understanding to substantively contribute to the theoretical discourse that shapes the broader landscape of family business dynamics. As we delve into this exploration, we anticipate our findings will not only enrich our understanding of the interplay between family names, family cohesion, and socioemotional wealth but also offer valuable insights for practitioners, policymakers, and scholars invested in the success and resilience of family-owned enterprises.